Theoretical analysis of the microwave radiation interaction with animals suffering from endometritis - Думанский, Александр Васильевич (Technology audit and production reserves, 2014)
Numerous veterinary studies show that electromagnetic treatments of endometritis in cows seems to be quite promising. However, it should be understood that the method involves creating a model describing the distribution of electromagnetic fields in different regions of animal body radiation at different frequencies, different power flux density and exposure time. However, the solution of this problem involves the overcoming major difficulties of theoretical and methodological nature. Based on the logical sequence of presentation and including electro-physical properties, in particular the permittivity of biological objects, we used the classical approach to calculate the structure of the electromagnetic field inside the uterus of cows when exposed to external electromagnetic fields. The main purpose of the theoretical calculations of the electromagnetic field microwaves inside the uterus of cows is to study their distribution in the volume of the object in order to treat endometritis by changing biotropic parameters. Using these calculated ratios a forecasting can be made that shows the impact of electromagnetic fields on certain areas of biological objects with different percentages of water.